Big Five Personality Traits dan Kesehatan Mental Remaja di Era Media Sosial - Muh Madhani Rahmatullah; Dealova Savara; Rizqika Ghina Salsabila; Fahma Ningrum Rahmasari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The rapid growth of social media has significantly influenced the psychological dynamics of adolescents, particularly regarding their mental health. This study aims to examine the relationship between the five dimensions of the Big Five personality traits (neuroticism, extraversion, openness, agreeableness, and conscientiousness) and adolescent mental health in the digital era. Using a qualitative method with a literature review approach, the study analyzed various recent scientific sources. The findings indicate that certain personality traits, such as high neuroticism, are positively correlated with mental health issues, while others, like extraversion and conscientiousness, serve as protective factors. The interaction between personality traits and social media usage patterns also affects adolescents' levels of stress, anxiety, and tendencies toward negative behaviors such as FOMO and digital addiction. These results highlight the importance of a personalized approach in supporting adolescents, involving parents, teachers, and counselors, to prevent psychological disorders and promote mental well-being based on individual personality characteristics.